Využití afinitní chromatografie pro studium působení vybraných oxysterolů u rostlin - Kamlar, Marek; Uhlík, Ondřej; Chlubnová, Ilona; Kohout, Ladislav; Harmatha, Juraj; Ježek, Rudolf; Šanda, Miloslav; Charvátová-Pišvejcová, Andrea; Macek, Tomáš (Chemické listy, 2010)
In plants, oxysterols brassinosteroids (BR) and ecdysteroids (ES) can be found. BR act as plant hormones with a positive effect on growth, stress tolerance or senescence. Their mechanism of action is based on signal transduction via a membrane receptor cascade, with or without assistance of oxysterol-binding proteins. The role of ES as insect hormones in plants is unknown. ES are likely to show an antifeedant effect on herbivorous pests, but other as yet unknown roles in plants are not excluded. A range of affinity carriers with immobilized synthetic analogues of plant BS and ES were prepared. Using these carriers, some proteins with affinity to the oxysterols were separated from cytosol extracts of plants. The proteins were assessed by electrophoresis and identified by sequencing. One of them is an osmotin-like protein precursor known as a pathogenesis- related protein. Another protein, RuBisCO, is known as the key enzyme in the Calvine cycle of the dark phase of photosynthesis. The interactions of these proteins with the oxysterols remain unclear.
Keywords: chromatografie afinitní; fytosteroly; kvantitativní vztahy mezi strukturou a aktivitou; Chromatography, Affinity; Phytosterols; Financing, Organized; financování organizované; Quantitative Structure-Activity Relationship